Caracterização do potencial genotóxico de porfirinas de base livre e metaloporfirinas de Zn (II) - Faria, Sophia Iwersen (2023)
Photodynamic therapy (PDT) is a treatment with several benefits, such as few side effects, ease of application and possible combination with other treatments. It is based on the production of reactive oxygen species (ROS) by a Photosensitizer (PS) upon irradiation. Due to their many desirable characteristics, porphyrins are often used as PS in PDT. Some of their attributes can vary, influencing its interaction with biomolecules of interest. In this work, four compounds were studied: TMePyP+, TPPS-, ZnTMe+ and ZnTTP-. Their interactions with DNA were evaluated through genotoxicity, ROS production and cytotoxicity. Results showed that cationic porphyrins were way more effective in inducing DNA damage, generating ROS and reducing cell viability than anionic ones. The zinc addition had little effect on those aspects, but caused the porphyrin to be selective towards tumours cells. Thus, this study provides insight on the role that charge and metal addition play in the interaction with DNA, and also that TMePyP+ and ZnTMe+ are promising candidates for use as PS in PDT.